"Moonlight Reflected on Many Thousands of Rivers": The Communicative Circuit of May Fourth. Issue 1 (3rd April 2019) - Zhang, Qing
Abstract: This article assesses the significance of technological development in early-20th-century China that created the communicative circuit for information sharing. The new media technology, allowed information to travel far and fast, creating not only a sense of belonging among the Chinese nationals, but also a network of collectivity among readers around the country.